Non-destructive testing using infrared image for the measurement of compressive strength of IBS concrete panel - Nur Nadzirah, Ahmad Ridzuan (2018)
This study is about developing a non-destructive testing method for the concrete panels especially for IBS concrete. The testing is for measuring the compressive strength of concrete without destructing the structure. There are two objectives for this study which is, to develop a non-destructive test measurement tool by using infrared analysis and to determine the correlation between compressive strength and heat distribution of concrete. The conventional and present method is destructing the structure where the concrete specimen will be compress until it achieves the maximum strength. This method will give the negative impacts to the structure that may be less in integrity due to the replacement of the structure where it may be has a different strength. It also may be less in aesthetic value because the structure had been cored. The method starts with making the samples of concrete cube sized 150mm x 150mm x 150mm which involving grade 20, grade 25, grade 30, grade 35 and grade 40 where each grade comes with nine samples that will be undergo testing at the age of 7th day, 28th day and 56th day. The testing involved are the non-destructive testing which is infrared thermal imaging and the destructive testing which is compressive strength test. The tools that have been use for non-destructive testing is infrared thermal camera which produce the thermal contour image. The destructive testing will be done right after the infrared thermal imaging to get the strength of the concrete. The thermal contour image then have been analysed into the software which are MATLAB and AutoCAD to get the non-destructive testing compressive strength reading. The collected data of infrared contour image then will be analysed to make the correlation of compressive strength and heat distribution of concrete between the different grades of concrete by measuring the diameter of the white, yellow, and orange colour of the contour produced by thermal contour image. The result found that the concrete below grade 25 are not suitable to use for this method as the reading of grade 20 is not relevant because the reading was not ascending as compared to the other grades of concrete. The result for the other grades of concrete show the ascending order of readings which can classify a good and an acceptable correlation coefficient because the reading of diameter for white, yellow and orange colour contour were 0.83, 0.97 and 0.98 respectively which are all near to the best fit reading which is 1. The tool of measuring the strength of concrete can be use in the Concrete Strength Measurement System that have been made just by uploading the thermal contour image into the software and run it to get the strength reading by their range reading of contour diameter. This study concludes that the new alternative method of non-destructive testing is an acceptable method to find the strength of concrete non-destructively. The correlation between compressive strength and heat distribution of concrete has been determined and it shows that the higher the strength of the concrete, the higher the heat distribution takes place in it.